2018
DOI: 10.1088/1748-9326/aabf21
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric jet response to Antarctic ozone depletion: An update with Chemistry-Climate Model Initiative (CCMI) models

Abstract: The Southern Hemisphere (SH) zonal-mean circulation change in response to Antarctic ozone depletion is re-visited by examining a set of the latest model simulations archived for the Chemistry-Climate Model Initiative (CCMI) project. All models reasonably well reproduce Antarctic ozone depletion in the late 20th century. The related SH-summer circulation changes, such as a poleward intensification of westerly jet and a poleward expansion of the Hadley cell, are also well captured. All experiments exhibit quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…However, Simpson & Polvani (2016) showed that the relationship is restricted to mainly the austral winter half-year, and that the theoretical basis originally proposed by Kidston & Gerber (2010) does not hold. Consistent with Simpson & Polvani (2016), both Seviour et al (2017) and Son et al (2018) found little effect of the mean jet latitude on the December-February jet response to polar stratospheric ozone depletion across different sets of global climate models. Furthermore, it is important to mention that factors other than the mean state also contribute to the uncertainty in the future SH jet response; previous studies have pointed to the roles of changes in the lower-and upper-tropospheric baroclinicity and in the polar stratospheric vortex (e.g.…”
Section: Introductionmentioning
confidence: 57%
“…However, Simpson & Polvani (2016) showed that the relationship is restricted to mainly the austral winter half-year, and that the theoretical basis originally proposed by Kidston & Gerber (2010) does not hold. Consistent with Simpson & Polvani (2016), both Seviour et al (2017) and Son et al (2018) found little effect of the mean jet latitude on the December-February jet response to polar stratospheric ozone depletion across different sets of global climate models. Furthermore, it is important to mention that factors other than the mean state also contribute to the uncertainty in the future SH jet response; previous studies have pointed to the roles of changes in the lower-and upper-tropospheric baroclinicity and in the polar stratospheric vortex (e.g.…”
Section: Introductionmentioning
confidence: 57%
“…New studies have reconfirmed these overall effects using different approaches based on observations and models. 68,69 Long-term data records show that changes in tropospheric circulation due to the ozone 'hole' have contributed to a decrease in summer temperatures over southeast and south-central Australia, and inland areas of the southern tip of Africa. 70 In the decades since the appearance of the ozone 'hole', anomalously high (or low) total ozone column amounts in the spring are significantly correlated with hotter (or colder) than normal summers over large regions of the SH.…”
Section: Shifting Of Climate Zonesmentioning
confidence: 99%
“…1) [80, 81, 84, 85, 91]. The causal chain for this starts with the fact that ozone absorbs solar radiation, and therefore in sunlit seasons, the depletion of stratospheric ozone induces local radiative cooling of the polar stratospheres [92].…”
Section: The Antarcticmentioning
confidence: 99%